PENGARUH MEDIA AUDIO VISUAL, MINAT BACA, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA SDN PAMEKASAN - Kholifah; Sulistyo; Onik Farida Ni’matullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low social studies learning outcomes of Pamekasan Elementary School students which only achieved 46.8% completeness, as well as the use of audio-visual media, reading interests, and learning motivation that still vary in the low to medium category. The purpose of this study is to analyze the influence of audio-visual media, reading interest, and learning motivation on social studies learning outcomes both simultaneously and partially. This study uses a quantitative approach with ex post facto methods and correlational techniques. The research population is all grade V students of SDN Cluster V, Pasean District, Pamekasan Regency which totals 62 students. The sampling technique uses total sampling. Data collection was carried out through a closed-ended questionnaire on the Likert scale to measure independent variables and documentation of social studies formative assessment scores to measure learning outcomes. Data analysis used multiple linear regression. The results of the study prove that audio-visual media, reading interest, and learning motivation simultaneously have a significant effect on social studies learning outcomes with an F value of 37.570 (sig. 0.000). The contribution of the three independent variables reached 66% to learning outcomes. Partially, learning motivation was the most dominant variable with a beta coefficient of 0.638, followed by audio-visual media of 0.377, and reading interest of 0.316. This study concludes that improving social studies learning outcomes requires integrated reinforcement on all three variables, with the main priority on student learning motivation.